EXPERIENCE OF APPLICATION HIGH PERFORMANCE CEMENT COMPOSITES FOR CREATING DURABLE SCULPTURAL ELEMENTS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Traditionally, sculptural and decorative elements of building facades are created from mortar mixes based on lime, gypsum or Portland cement. Generally these materials have porous and permeable structure, which determines their accelerated degradation, especially in the aggressive environment of modern cities. High performance cement composites (HPCC) have been considered for production and restoration of sculptural elements in historical buildings. For this purpose, fine-graded, multi-component and highly workable mixes were elaborated. Mix compositions were modified with micro-fillers, plasticizing and stabilizing admixtures, as well as fibers to improve material ductility and control shrinkage cracking. Basic mechanical properties and durability (such as water absorption, frost resistance) were determined and two types of HPCC were compared (>50 MPa: HPCC and >120 MPa: UHPCC). It has been confirmed that cement composite mixes are characterized by self-consolidating effect, high compressive strength, extremely high resistance versus freezing and thawing cycles and low water absorption. Surface quality was evaluated and initial water absorption (tube tests) were performed for laboratory samples and real sculptural elements after 5 years of exploitation. The results confirmed good potential for using HPCC for creating more attractive and durable architectural shapes and façade elements compared to elements made using traditional cement and lime mortar.